Словник мови творчої особистості: принципи укладання реєстру (з прози Ю. Андруховича) - Тищенко, О. (Лексикографічний бюлетень, 2017)
The author’s dictionary is an intermediate form of fixing vocabulary and phraseology on their way to fundamental dictionaries. The purpose of the Dictionary of Creative Personality Language is to collect, systematize and describe new phenomena of the Ukrainian language, first of all lexical and phraseological units not certified by dictionaries of a certain type and / or period, their forms and meanings – lexicographic innovations – as a basis for complex neological dictionary. fundamental dictionary of the Ukrainian language. Thus, the materials of this dictionary, which compare samples of individual and collective (usual) language practice, will be a mediator between the author’s text and the active common language dictionary of the Ukrainian language.